Male Reproductive Health - Wu, Wei; Ziglioli, Francesco; Maestroni, Umberto (IntechOpen, 2020)
Male reproductive health is an important area affecting men's overall health and well-being. Infertility is a worldwide problem that affects approximately 15% of married couples. Half of these cases can be traced to male partners. Infertile men are at an elevated risk of cancer development later in life, primarily genitourinary malignancies such as testicular and prostate cancer. This book will focus on male reproductive health, from the aspects of semen quality, male infertility, testicular cancer, and prostate cancer, and their detection, diagnosis, treatment, and prevention.